2014
DOI: 10.1177/0004867413520253
|View full text |Cite
|
Sign up to set email alerts
|

Regional brain volumes in body dysmorphic disorder compared to controls

Abstract: This is the largest volumetric neuroimaging study in BDD to date and provides important data on volumetric differences that implicate fronto-limbic circuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 38 publications
1
16
1
2
Order By: Relevance
“…The absence of significant abnormalities in brain volumes agrees with one previous morphometric study in BDD (Feusner et al, 2009), but not with three other studies (Rauch et al, 2003; Atmaca et al, 2010; Buchanan et al, 2014). Three out of the four previous studies found no abnormalities in total GM (Rauch et al, 2003; Feusner et al, 2009; Atmaca et al, 2010), while one found lower total GM in BDD patients, compared with controls (Buchanan et al, 2014).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…The absence of significant abnormalities in brain volumes agrees with one previous morphometric study in BDD (Feusner et al, 2009), but not with three other studies (Rauch et al, 2003; Atmaca et al, 2010; Buchanan et al, 2014). Three out of the four previous studies found no abnormalities in total GM (Rauch et al, 2003; Feusner et al, 2009; Atmaca et al, 2010), while one found lower total GM in BDD patients, compared with controls (Buchanan et al, 2014).…”
Section: Discussionsupporting
confidence: 77%
“…Three out of the four previous studies found no abnormalities in total GM (Rauch et al, 2003; Feusner et al, 2009; Atmaca et al, 2010), while one found lower total GM in BDD patients, compared with controls (Buchanan et al, 2014). Two studies found greater total WM volume in BDD (Atmaca et al, 2010; Rauch et al, 2003), although two other studies did not (Buchanan et al, 2014; Feusner et al, 2009). Contrary to our hypotheses, we did not find abnormalities in the anterior cingulate and the orbitofrontal cortices, despite findings in two previous studies of smaller volumes in these regions (Atmaca et al, 2010; Buchanan et al, 2014), nor did we find abnormalities in visual processing regions.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations